Diagnosis of sudden death using postmortem CT. (December 2020) - Kondou, Hiroki; Tsuboi, Hajime; Takazakura, Ryutaro; Nakamura, Mami; Bandou, Risa; Ichioka, Hiroaki; Idota, Nozomi; Ikegaya, Hiroshi
Highlights: The relationships between postmortem CT findings in the heart and great vessels and sudden death were examined in this study. The CT findings of fluid–fluid level were significantly associated with sudden death cases. The diagnostic sensitivity of fluid–fluid level for sudden death was 82.7%, with a specificity of 88.4%. Postmortem CT may be of value to distinguish between cases of sudden death and non-sudden death. Abstract: Purpose: The judgement of "sudden death" or "non-sudden death" is important in forensic diagnosis. Although postmortem computed tomography (PMCT) is widely used to determine the course of death, judgement of sudden death or non-sudden death based on PMCT findings has not been examined. The relationships between PMCT findings in the heart and great vessels and sudden death (SD) were examined in this study. Methods: We evaluated the blood characteristics of 182 (139 SD and 43 non-SD) forensic cases using not only PMCT but also an autopsy. In the PMCT examination, we observed the findings of six intravascular regions: the ascending aorta, the aortic arch, the descending aorta, the right atrium, the right ventricle, and the pulmonary artery trunk. In the SD cases, at least one region showed the fluid–fluid level (FFL) through PMCT imaging, while the autopsy showed the cadaveric blood fluidity. Results: The CT findings of FFL were significantly associated with SD cases ( p < 0.05). In total, 115 of the 139 SD cases expressed FFL, and 38 of the 43 non-SD cases showed non-FFL findings via PMCT. The diagnostic sensitivity of FFL for SD was 82.7%, with a specificity of 88.4%. Conclusion: These results suggest that PMCT imaging is useful for the diagnosis ofSD.